COMPARISON OF ENGLISH PROFICIENCY IMPROVEMENT AMONG SELECTED FRESHMEN IN UNIVERSITAS ADVENT INDONESIA (UNAI) - Cherrilyne Goodenough; Caroline V. Katemba (Journal of Language Pedagogy, 2011)
This study compared the improvement in English proficiency of freshmen who undertook theRemedial English and English I classes concurrently (Group A) with that of freshmen whohad marginally better English proficiency scores and undertook the English I class only(Group B). The paired samples t-test on the gain scores resulted in a t-observed value of2.604 at a significance level a = 0.05, thus the conclusion that Group A achieved betterimprovement in English language proficiency than Group B.